Pulmonary Hypertension in Pregnancy - A fatal combination - Wijerathne, C N; Kaluarachchi, A; Senanayake, H M; Rodrigo, N; Seneviratne, H R (My University, 2012)
Introduction : Primary Pulmonary Hypertension (PPH) in pregnancy is "associated with a high maternal mortality. Eisenmenger's Syndrome in pregnancy has a reported incidence of maternal mortality of 52%. Fourteen patients with severe pulmonary hypertension complicating pregnancy who were manased by the University Obstetrics Unit. Colombo are descnbecL Methodology : Five patients with PPH were refered 'o us at an average POG of 22 weeks. Four were diagnosed during the antenatal period, while one was transferred in her second pregnancy for suspected cervical incompetence. The latter been diagnosed to have PPH during her first pregnancy the year before! Six patients had Eisenmenger's Syndrome; four had atrial septal defect (one in her 7th pregnancy) and 2 had ventricular septal defect. Two patients had Cor Pulmonale and one had Obesity - Hypoventilation Syndrome. A ll patients were kept "in - ward" throughout pregnancy with oxygen inhalation, bed rest, subcutaneous heparin and frequent cardiovascular monitoring. Termination of pregnancy by Caesarean Section was considered at 35 weeks'POG or earlier if cardiac decompensation occurred. Results : All those with PPH were terminated at 35 weeks POG by elective lower segment caesarean section and sterilized ( 3 under local anesthesia and 2 under epidural anaesthesia). Three of these women succumbed within 48 hour of delivery. Of those with Eisenmenger's Syndrome, 3 underwent elective caesarean section at 36 weeks of whom one succumbed at 3 weeks post partum. One had a death -in - utero at 32 weeks. Two were terminated at mid-trimester by hysterotomy due to cardiac decompensation and succumbed 24 hours po§t delivery. Of those with Cor Pulmonale one had respiratory arrest with the onset of labour at 33 weeks. The other needed termination at 29 weeks and died 36 hours post delivery. The patient with ObesityHypoventilation was terminated at 26 weeks and survived upto 5 months post partum when she died of secondary respiratory failure. The eight maternal deaths described contributed to the total of 11 maternal deaths in our unit during this period. Conclusion : Pulmonary Hypertension in pregnancy has a high risk of liMttiual and fetal death and should be avoided whenever possible by pre-conception counselling and termination in early pregnancy.